2021
DOI: 10.1186/s12889-021-10707-x
|View full text |Cite
|
Sign up to set email alerts
|

“We are in this together:” dyadic-level influence and decision-making among HIV serodiscordant couples in Tanzania receiving access to PrEP

Abstract: Background A substantial number of new HIV infections in sub-Saharan Africa occur within stable couples. Biomedical prevention (pre-exposure prophylaxis, PrEP) and treatment (antiretroviral therapy, ART) can provide benefits to sexual partners and can be used to prevent infection within HIV serodiscordant couples. However, research is typically focused on individuals, not dyads, even when the intervention may directly or indirectly impact sexual partners. Gaps remain in understanding best pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…This systematic review suggests that couple-based interventions have a stronger effect than individual-level interventions to boost condom use and encourage HIV testing among couples in RCTs. One possibility is that behavioral cooperation may help couples establish common goals in initiating healthy behaviors and developing a partnership based on joint decision-making and collective action toward reducing HIV transmission risks [ 13 ]. When both partners participate in couple-based interventions, they decrease discrepant perceptions of HIV transmission risks and increase their health literacy regarding HIV [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This systematic review suggests that couple-based interventions have a stronger effect than individual-level interventions to boost condom use and encourage HIV testing among couples in RCTs. One possibility is that behavioral cooperation may help couples establish common goals in initiating healthy behaviors and developing a partnership based on joint decision-making and collective action toward reducing HIV transmission risks [ 13 ]. When both partners participate in couple-based interventions, they decrease discrepant perceptions of HIV transmission risks and increase their health literacy regarding HIV [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from prior research supports our findings that CHCT has been recognized as one of the most cost-effective intervention strategies in resource-constrained settings and is particularly strong in HIV-serodiscordant couples [ 43 ]. This may be explained by the mobilizing of shared resources within a couple that were previously rarely considered, including the awareness of the importance of sexual negotiation, and supporting once-scarce environmental resources such as the space for an open and private conversation with a trained counselor for CHCT and/or access to PrEP [ 12 , 13 ]. Although the evidence for cost-effectiveness analyses of skill-building intervention components remains to be clarified, future public health intervention strategies need to be weighted more toward resource-constrained areas with the objective to more effectively reduce HIV risk among couples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few interventions have attempted to capitalize on family member roles and interactions to achieve appropriate family-wide risk communication [23]. Researchers have applied family systems theories to a variety of other health contexts including HIV-discordant couples [24], partners' smoking cessation [25][26][27][28], lung cancer patients' family members who smoke [29], and mother-daughter pairs for sexually transmitted infections prevention [30]. However, surprisingly little research has applied this thinking to family communication regarding risk assessment such as family history (e.g., Koehly et al [31]) or for people identified as high risk for hereditary breast and ovarian cancer (e.g., Peters et al [32]).…”
Section: Introductionmentioning
confidence: 99%
“…Positive and equitable predisposing characteristics can lead to a transformation of motivation and in turn, allows a couple to engage in communal coping where they cooperatively engage in health‐enhancing behaviours (e.g. MPT use) [ 43 , 44 , 45 , 46 , 47 ]. Given the importance of male partner involvement for many women and the potential for more open communication in relationships to increase HIV prevention and contraceptive use, facilitating equitable decision‐making processes that lead to the transformation of motivation among couples constitutes a promising strategy to support future MPT use.…”
Section: Introductionmentioning
confidence: 99%